2013
DOI: 10.1542/peds.2012-0880
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Determine the Likely Age of an Adolescent’s First Drink of Alcohol

Abstract: Adding variables to those from our original study improved our ability to model the likely age of alcohol initiation. In addition to the SSAGA, the YSR appears to have utility as a research tool to predict the age of alcohol initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
5
26
0
Order By: Relevance
“…Early SI might represent significant depressed mood which may also reduce the chance that individuals will interface with delinquent peer groups (potentially, due to peer rejection) who might have otherwise promoted substance use (Hussong et al, 2011). In fact, a prior study of these data show similar protective effects of a score assessing difficulties with family and peers on age of onset of alcohol use (Kuperman et al, 2013). This hypothesis is also supported by the stronger correlation between MDD and SI (r = 0.74) rather than SA (r = 0.52).…”
Section: Discussionsupporting
confidence: 54%
“…Early SI might represent significant depressed mood which may also reduce the chance that individuals will interface with delinquent peer groups (potentially, due to peer rejection) who might have otherwise promoted substance use (Hussong et al, 2011). In fact, a prior study of these data show similar protective effects of a score assessing difficulties with family and peers on age of onset of alcohol use (Kuperman et al, 2013). This hypothesis is also supported by the stronger correlation between MDD and SI (r = 0.74) rather than SA (r = 0.52).…”
Section: Discussionsupporting
confidence: 54%
“…However, in a later study, this group did not replicate this relationship but did demonstrate an association between this SNP and the YSR externalizing score (Dick, Aliev, Latendresse, Hickman, et al, 2013). This potential relationship between disruptive behavior and rs279871 builds upon our previous work demonstrating significance for both the number of CD symptoms and the YSR externalizing score as predictors for the age of drinking initiation (Kuperman et al, 2013) and provides further support for using rs279871 to determine whether it improves our previous model.…”
Section: Introductionsupporting
confidence: 64%
“…From this pool, 3 variables – age at interview, number of DSM-IV non-drinking related conduct disorder symptoms (referred to as CD from this point), and the number of adult alcohol-dependent (AD) siblings – formed the most parsimonious model and explained 45% of the variance of age of first drink. Kuperman et al (2013) subsequently employed these variables along with two additional SSAGA variables (whether most of a subject's best friends drank, and if the subject smoked a cigarette before initiating drinking) and eight scale scores from the commonly used Achenbach Youth Self Report (Achenbach & Rescorla, 2001) to predict the onset of alcohol initiation in an independent sample of 820 adolescent COGA subjects (∼60% had not initiated drinking) utilizing the Cox proportional hazards models. Four of these Achenbach Youth Self Report (YSR) scales were hypothesized to be protective and decrease the risk for drinking initiation (positive qualities, activities competence, social competence, and school competence), and four were predicted to be harmful and increase the risk for alcohol initiation in this young cohort (externalizing, attentional, social problems, and internalizing scores).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent work modeling the factors most closely associated with alcohol use initiation indicated that, although FH and indicators of behavioral under-control were important, they did not constitute the entire set of pertinent variables. Of perhaps no surprise to persons working with adolescents was the fact that the most powerful variable was whether the best friends of these adolescents drank [12]. …”
Section: Resultsmentioning
confidence: 99%